Konsep Dasar Menejemen Pendidikan di Madrasah Aliyah - Anis Zohriah; Salimah Salimah; Nurul Fika; Machdum Bachtiar (Departement of Mathematics Education, 2023)
The basic concept of education management is a hot topic of discussion and is the center of attention among educators and education staff. The issues to be discussed in this study are the urgency of education management the meaning of education menegement, the goal education menegement, the function of education management, the education menegemen model, the development management theory and educational management issues. The method used in this research is qualitative research with a literature study approach in the literature study educationtmanagement functions, education management models, management theory devlopments and management issues.